An Analysis of Language Styles in the Movie “Instant Family” - Ni Kadek Ayu Siska Sinta Dewi; I Made Perdana Skolastika (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study analyzes the language styles in the movie "Instant Family," a drama directed by Sean Anders and released on Netflix on January 19, 2019. Language style variation is a natural aspect of communication, influenced by social contexts and interlocutors. In "Instant Family," these variations are explored to understand how writers and speakers use language choices, sentence structures, and situational contexts to convey meaning. The research employs a qualitative content analysis approach, involving repeated viewings of the film to identify and categorize language styles based on Martin Joos’ theory: frozen, formal, consultative, informal, and intimate. Each dialogue instance is analyzed in relation to its context and character relationships to illustrate the use of different language styles in character development and emotional expression. The study's descriptive qualitative design reveals five distinct language styles. Analysis identifies thirty instances of these styles within the movie's dialogues, with formal style being the most prevalent, appearing eleven times. This predominance is attributed to the numerous public exchanges led by the protagonist, particularly in scenes involving interactions between the presiding officer and the accused. The study suggests that English Department students further investigate language styles across various sources, including movies, novels, social media, and articles. Analyzing linguistic styles in "Instant Family" is crucial for understanding how language choices shape character development and thematic expression. This research serves as a foundation for future studies in film and communication, exploring the impact of linguistic styles on audiences and narratives